Nonadiabatic Effect on the Rescattering Trajectories of Electrons in Strong Laser Field Ionization Process - 涂心海 郝小雷 李卫东 胡师林 陈京 (Chinese physics letters, 2016)
The important features of the rescattering trajectories in strong field ionization process such as the cutoff of the return energy at 3.17Up and that of the final energy at 10Up are obtained, based on the adiabatic approximation in which the initial momentum of the electron is assumed to be zero. We theoretically study the nonadiabatic effect by assuming a nonzero initial momentum on the rescattering trajectories based on the semiclassical simpleman model. We show that the nonzero initial momentum will modify both the maximal return energy at collision and the final energy after backward scattering, but in different ways for odd and even number of return trajectories. The energies are increased for even number of returns but are decreased for odd number of returns when the nonzero （positive or negative） initial momentum is applied.